2010
DOI: 10.1016/j.rbmo.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Serum inhibin A concentration in women with polycystic ovarian syndrome and the correlation to ethnicity, androgens and insulin resistance

Abstract: A prospective case-series in an academic hospital clinic was performed to determine whether there is a relationship between polycystic ovarian syndrome (PCOS) and ethnicity. Also, serum inhibin A concentrations were compared between PCOS and normal-ovulatory women. The possibility of a correlation between inhibin A, androgens and insulin resistance in PCOS women was evaluated. Serum inhibin A concentrations were measured in anovulatory PCOS patients (n=32) and in control women of reproductive age (n=16). Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
(40 reference statements)
1
10
1
2
Order By: Relevance
“…Resistin plasma levels have been co rrelated with fasting glucose and HOMAIR in PCOS wo men [60] . Inhibin A levels in PCOS women were not found to correlate with IR in PCOS women [61] . Most of these serum markers share common limitations and have been poorly studied.…”
Section: Assessment Of Insulin Resistancementioning
confidence: 77%
“…Resistin plasma levels have been co rrelated with fasting glucose and HOMAIR in PCOS wo men [60] . Inhibin A levels in PCOS women were not found to correlate with IR in PCOS women [61] . Most of these serum markers share common limitations and have been poorly studied.…”
Section: Assessment Of Insulin Resistancementioning
confidence: 77%
“…Studies conducted with adults have yielded controversial results. While some have shown that INH-A does not change in patients with PCOS (20,21), other studies have shown an increase (22,23,24), while some other studies reported a decrease (25,26,27). Some studies have shown that INH-B level increases in patients with PCOS (28), whereas others have shown that it decreases (30).…”
Section: Discussionmentioning
confidence: 93%
“…However, conflicting results have been reported in studies conducted on adult women. Some studies have shown that INH-A does not change in patients with PCOS (20,21), whereas others have shown that it increases (22,23,24) or decreases (25,26,27). There are also similar controversial results related with INH-B levels (20,21,27,28,29,30).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to triple test parameters, the quadruple test includes inhibin-A. However, Segal et al found that serum inhibin-A concentration in women with PCOS was lower than normalovulatory women [1,2].In addition, Karsli et al investigated biochemical parameters in the first trimester aneuploidy screening test in the pregnant women with and without PCOS. The biochemical components PAPP-A and fβ-hCG were found to be significantly lower in the PCOS group compared to control group [3].…”
mentioning
confidence: 99%
“…In addition to triple test parameters, the quadruple test includes inhibin-A. However, Segal et al found that serum inhibin-A concentration in women with PCOS was lower than normalovulatory women [1,2].…”
mentioning
confidence: 99%